STRATEGI SISTEM PENANGANAN IKAN TUNA SEGAR YANG BAIK DI KAPAL NELAYAN HAND LINE PPI DONGGALA - Mboto, Normawati K; Nurani, Tri Wiji; Wisodo, Sugeng Hari; Mustaruddin, Mustaruddin (Jurnal Teknologi Perikanan dan Kelautan, 2015)
There is increasing demand for high quality products at a competitive price. Tuna is a prime commodity with strict quality standards. The research question addressed is whether the tuna handling system used by hand line fishermen operating out of Donggala fishing port (PPI Donggala) is still poor, affecting quality and thus lowering the market value of the fish they catch. The goal of this research was to contribute towards improvements in tuna handling by hand line fishermen from the Donggala fishing port. Thus the main benefit should be an improvement in the quality of the fish landed. The research was carried out during April-May 2014 at the Donggala fishing port in Central Sulawesi. Data were collected through observation and interviews. Data were collected from representative individuals through purposive sampling. Both primary and secondary data were collected. Analysis of data was undertaken with the approach strengths weaknesses opportunities threats (SWOT) analysis it of a training strategies the handling of the good fish on board. Based on of the analysis (SWOT) produced four strategies. The strategy was SO, ST, WO and the strategy WT. The fourth strategy is good to be applied, but see the position of the system is in a quadrant five (v), then the most appropriate strategy is WO and ST. The combination strategy WO are increased knowledge about the quality and skill handler’s tuna fish. Another thing that needs to be done that is the addition of the tools like ring tuna dan killing spike. Ring the functioning to hold the movement of the process of hauling and killing spike to deadly fish tuna. Combination strategy that is making ST it self standard operating prosedure (SOP) handling of good; as well as improving work competence.